Level And Dispersion of Satisfaction in Teams: Using Foci and Social Context to Explain the Satisfaction-Absenteeism Relationship - Dineen, Brian R.; Noe, Raymond A.; Shaw, Jason D.; Duffy, Michelle K.; Wiethoff, Carolyn (Academy of Management Journal, 2007)
We develop an integrative theory regarding the effects of mean levels and dispersion of satisfaction predicting absenteeism. Differential interactive predictions are derived for two satisfaction foci and tested in two distinct samples. Among student teams, absenteeism from team meetings was highest when team (internally focused) satisfaction mean and dispersion were both lower, but low when course (externally focused) satisfaction mean and dispersion were both lower. Moreover, given lower dispersion, the mean team satisfaction-absenteeism relationship appeared stronger, whereas the same relationship involving course satisfaction appeared weaker than meta-analyzed individual-level relationships. We replicated these results among manufacturing teams using team and job satisfaction foci.